Clinical researchProhepcidin and its possible role in anaemia of pregnancy - Rams, Leszek; Drozdowska-Rams, Lena; Małyszko, Jacek; Pawlak, Krystyna; Małyszko, Jolanta (Archives of Medical Science, 2008)
Introduction: Hepcidin is the predominant negative regulator of iron absorption in the small intestine, iron transport across the placenta, and iron release from macrophages. The aim of the study was to assess prohepcidin levels in pregnant women in relation to anaemia, inflammatory cytokines and iron status. Material and methods: The studies were performed on 37 healthy pregnant women (third trimester), 34 anaemic pregnant women (third trimester), 20 healthy pregnant women (first trimester) and 30 healthy female volunteers. Prohepcidin, hsCRP, soluble receptor of transferrin (sTfR) and interleukin-6 were studied using commercially available kits. Results: Prohepcidin was higher in pregnancy, namely in anaemic patients, than in healthy females. In anaemic pregnant females prohepcidin showed a correlation with haemoglobin, haematocrit and total protein. In pregnant females in the first trimester prohepcidin was related to hsCRP. In all non-anaemic pregnant women (first and third trimester) prohepcidin correlated with sTfR and ferritin. In healthy volunteers prohepcidin was related to ferritin. Conclusions: Elevated prohepcidin in pregnancy related to ferritin and sTfR may reflect an acute phase reaction, and either the cellular need for iron or the rate of erythropoiesis. In anaemia in pregnancy a cause-effect relationship between haematocrit and hepcidin might exist. A rise in prohepcidin in pregnancy may also be due to the fact that some proinflammatory cytokines play a fundamental role in inducing hepcidin gene expression, namely IL-6.